Experimental Investigation of Seismic-Induced Hydrodynamic Pressures on a Vertical Wall under Conditions of Wave Resonance. (6th September 2017) - Zhou, YiLiang; Yao, LingKan; Gao, MingYuan; Ai, Hongzhou
Abstract : The distribution of hydrodynamic pressure acting on the structural face of a dam significantly influences the stability of the dam. The present study investigates the development of the hydrodynamic pressure acting on the surface of a dam at different heights with respect to time during earthquakes with different dominant frequencies using a shaking table. The results demonstrate that the variation in the hydrodynamic pressure significantly follows the seismically accelerated wave motion in the absence of resonance. However, under conditions of resonance, the fluctuations in the hydrodynamic pressure exhibit similarities with a sine wave, and the positive peak values present some hysteresis. The experimental pressure values in the absence of resonance present parabolic distributions with respect to the water height that are in good agreement with the corresponding hydrodynamic pressures determined by Westergaard's equation, while conditions of wave resonance produce a uniform distribution of hydrodynamic pressures with greater values and much longer periods of increased hydrodynamic pressure than the case of nonresonance. In addition, the seismic frequency, fundamental frequency of the reservoir, maximum peak seismic acceleration, and initial water depth are treated as variables. An empirical equation is derived to predict the maximum hydrodynamic pressure in conjunction with wave resonance conditions.